Possible relationship between blood groups and impacted lower third molars categorized according to Pell and Gregory and Winter classifications - Gulsen, Ibrahim Tevfik; Cimen, Tansu (Vojnosanitetski pregled, 2026)
Background/Aim. Teeth that fail to reach their normal position within the jaws are considered to be impacted, and the etiology of impacted teeth is multifactorial. The aim of this study was to examine the possible relationship between blood groups and classifications of impacted lower third molars (LTMs) according to the Pell and Gregory’s and Winter’s classifications. Methods. This retrospective, cross-sectional study included 534 patients (274 males and 260 females) with at least one impacted LTM. A total of 890 LTMs were assessed using panoramic radiographs. Teeth were classified based on Pell and Gregory’s and Winter’s classifications., and blood groups were documented for each patient. Statistical analysis was performed using Fisher-Freeman-Halton test and Fisher’s exact test, with the Bonferroni correction Z test for multiple comparisons. Results. Significant relationships were identified between blood groups and the Pell and Gregory classification (p = 0.008), but not with the Winter classification. Notably, women with A Rh-negative (Rh-), AB Rh-, and B Rh- blood groups exhibited higher prevalence rates for the I/B, I/C, and III/C positions, respectively. Additionally, women with A Rh-positive (Rh+) and O Rh+ blood groups demonstrated higher prevalence rates for the II/A position, while men with A Rh+ showed higher rates for the II/C position. Gender-specific differences in impaction patterns were observed for A Rh+ and O Rh+ blood groups (p = 0.006, p = 0.038, respectively). Conclusion. Blood group antigens might influence LTM impaction patterns, particularly in relation to Pell and Gregory classification.
Keywords: blood group antigens; molar, third; radiography, panoramic; tooth, impacted.